Dialogic peer coaching as teacher leadership for professional inquiry. Issue 2 (6th June 2014) - Charteris, Jennifer; Smardon, Dianne
Abstract : Purpose: – Dialogic peer coaching as leadership can enable teachers to influence each other's professional learning. The purpose of this paper is to shift the emphasis from the role associated with the designated title of leader to the purpose and relevance of teacher leadership in the context of dialogic peer coaching. Design/methodology/approach: – The research was undertaken as a small qualitative case study embedded in a school-based, teacher professional development project. Nine groups of peer coaches from five unrelated schools engaged in a formal process of collaborative inquiry over two years. Interview data from 13 volunteer teacher participants were analysed using the constant comparison method and themes determined. Findings: – The study revealed that there was growth in teacher leadership capabilities as they become dialogic peer coaches to each other. Practical implications: – Through their collaborative peer coaching dialogue teachers have the transformative space to articulate their thinking. They can engage in dialogic feedback where they are positioned as experts in their own practice. Social implications: – The teachers in this study are positioned within communities of practice as co-constructers of knowledge and co-learners. On the basis of the findings the authors suggest that this can support the development of high capacity leadership in schools. This stance contrasts with a technicist approach to teacher professional learning in which teachers are situated as absorbers or recipients of knowledge constructed elsewhere. Originality/value: – The research reported in this paper addresses three key elements of leadership: individual development; collaboration or team development; and organisational development. It outlines a means by which teacher leadership can be strengthened to address these elements in schools.